Working together? Synergies in government and NGO roles for community forestry in the Indian Himalayas. (February 2019) - Gupta, Divya; Koontz, Tomas M.
Highlights: We analyzed roles of government and NGOs in community forestry in India. We found that convergence of the government and NGOs can produce synergies. We found that NGOs direct communities to the resources provided by the government. Abstract: Community forestry literature promotes the idea that self-governance and self-organization lead to successful forest governance. However, this assumption marginalizes the different roles that external agents can play in organizing the communities to form forest institutions, engage in different outreach and capacity building activities and serve as a source of different kinds of resources. Given the increasing visibility of government and non-governmental organizations in community-based natural resource management, we believe it is important to understand the specific roles and impacts that convergence of these actors have on community efforts in resource governance. In this study, we first investigate the roles of government and non-governmental organizations and then conduct a comparative analysis of those roles to demonstrate synergies that emerge between government and NGOs in local forest governance. We find that while the government mainly provided technical and financial support, it is the NGOs that directed the communities to those resources. Our conclusions highlight that although the government and NGOs work within certain constraints, their convergence can make up for each other's limitations and synergistically facilitate community efforts in forest governance.